Design of Trickle Irrigation System for Peppers (Capsicum annum var. Longum L.) at Resinda Project, Karawang - Elphyson T; Nora H. Pandjaitan; . Prastowo (PERTETA, 2000)
Trickle irrigation is an irrigation method which can give continuous water drops at the root zone. The main components of Trickle Irrigation System are : emitter. lateral pipe, manifold pipe, main pipe, water pump and other supporting components.The design is using point source type of emitter. Each emitter serves 4 pepper plants. The total power consumption at pump station III is 8.4 KW. The total operation of pump station I is 752.I hrs/ season, pump station II is 2256.2 hrs / season and pump station III 1504.I hrs / season.